Stability properties of some port-Hamiltonian SPDEs - Kuchling, Peter; Rüdiger, Barbara; Ugurcan, Baris (arXiv)
We examine the existence and uniqueness of invariant measures of a class of stochastic partial differential equations with Gaussian and Poissonian noise and its exponential convergence. This class especially includes a case of stochastic port-Hamiltonian equations.